2021
DOI: 10.3349/ymj.2021.62.7.569
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Locoregional Recurrence after Radical Cystectomy for Stage T3-4 Bladder Cancer: A Radiation Oncologist's Point of View

Abstract: Purpose Adjuvant radiotherapy (RT) has been performed to reduce locoregional failure (LRF) following radical cystectomy for locally advanced bladder cancer; however, its efficacy has not been well established. We analyzed the locoregional recurrence patterns of post-radical cystectomy to identify patients who could benefit from adjuvant RT and determine the optimal target volume. Materials and Methods We retrospectively reviewed 160 patients with stage ≥ pT3 bladder can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Some studies have confirmed that female sex is associated with worse CSS outcomes, indicating a potentially poorer prognosis for women with MIBC [17,18]. Another study has suggested that female sex is associated with a higher rate of local-regional cancer control failure in high-stage bladder cancer patients after RC [19]. One hypothesis is that altered androgen levels in women may contribute to earlier tumor progression and higher metastatic potential, leading to inferior survival outcomes compared to men [17].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have confirmed that female sex is associated with worse CSS outcomes, indicating a potentially poorer prognosis for women with MIBC [17,18]. Another study has suggested that female sex is associated with a higher rate of local-regional cancer control failure in high-stage bladder cancer patients after RC [19]. One hypothesis is that altered androgen levels in women may contribute to earlier tumor progression and higher metastatic potential, leading to inferior survival outcomes compared to men [17].…”
Section: Discussionmentioning
confidence: 99%